Dampak Media Sosial Yang Mempengaruhi Etika Perilaku Dan Gaya Komunikasi Mahasiswa/I Fakultas Ilmu Sosial Universitas Islam Negeri Sumatera Utara - Batubara, Viandra Fahira Ramadhani; Haura Putri Aqillah; Ghefira Nur Azzahra; Nelpianti Siregar; Surya Alfi Rozi siregar; Nursapia Harahap (Journal of Social Science and Humanities, 2024)
The presence of social media as a means of communication, directly or indirectly, and influences community life. Because it provides opportunities for users to interact and convey aspirations and inspiration, it can even affect the communication style of social media users. This study aims to determine the impact of social media on the behavior and communication style of students of the Faculty of Social Sciences, State Islamic University of North Sumatra. The type of research is quantitative descriptive analysis. This research was carried out on campus IV of the State Islamic University of North Sumatra. The subjects in this study are 31 students of the Faculty of Social Sciences. Data was collected with a questionnaire instrument using a Likert scale. The data collection instrument uses an online questionnaire to students and the data is analyzed by a descriptive method. The results showed that the average of 10 student questionnaire questions female students of the Faculty of Social Sciences 75, 24% with the criteria of agreeing.